Successful Control of Hypoglycemia with Pasireotide LAR in a Patient with Inappropriate Insulin Secretion - Rouland A; Bouillet B; Legris P; Simoneau I; Petit JM; Vergès B (Dove Medical Press, 2021)
Alexia Rouland,1 Benjamin Bouillet,1,2 Pauline Legris,1 Isabelle Simoneau,2 Jean-Michel Petit,1,2 Bruno Vergès1,2 1Endocrinology Diabetics and Metabolic Disorders Department, Dijon University Hospital, Dijon, France; 2French National Health and Medical Research Body Unit, Lipid-Nutrition-Cancer-1231, University of Burgundy, Dijon, 21000, FranceCorrespondence: Alexia RoulandEndocrinology Diabetics and Metabolic Disorders Department, Dijon University Hospital, 14 Rue Paul Gaffarel, Dijon, 21000, FranceEmail alexia.rouland@chu-dijon.frIntroduction: Inappropriate insulin secretion could be due to several diseases. Nesidioblastosis is characterized by diffuse hyperplasia of pancreatic beta cells, causing organic hypoglycemia. No pancreatic lesions are found on the imaging of patients with this condition. Diazoxide is used as a first-line treatment but can be poorly tolerated because of its side effects, and therapeutic failure is possible. Somatostatin analogues have limited efficacy because of their poor affinity to somatostatin (SST) receptors. Pasireotide is a somatostatin analogue with a much higher affinity to SST receptors, especially SST5, and it could thus be more efficient for treating nesidioblastosis-related hypoglycemia.Observation: A 56 years-old diabetic woman had symptoms of hypoglycemia, persistent after treatment’s withdrawal. A fasting test authentify an organic hypoglycemia, at 34mg/dL, a plasma insulin level at 6mUI/L above the 5 mU/L threshold, a C-peptide level at 1.9 ng/mL above the threshold of 0.6, and an insulin/C-peptide ratio 0.066, below the threshold of 1. No lesions were found on CT-scan or endoscopic ultrasound. Somatostatin receptor scintigraphy was also negative. Diazoxide and octreotide failed to improve the recurrence of hypoglycemia episodes. With pasireotide LAR, hypoglycemia disappeared and glycemia increased. Hyperglycemia was controlled with sitagliptin. The patient has now been treated with pasireotide LAR for two years, with no more episode of hypoglycemia until now.Discussion: We present the first case of nesidioblastosis treatment with pasireotide LAR, with success. Patients diagnosed with nesidioblastosis and diazoxide-resistant hypoglycemia, or who experience difficulties with other treatments, could use pasireotide LAR in conjunction with glycemia monitoring, particularly if they are diabetic.Keywords: nesidioblastosis, hypoglycemia, pasireotide LAR, diazoxide